2009
DOI: 10.1128/jb.01313-08
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin, Capsule, and Bacterial Attachment Contribute to Neisseria meningitidis Resistance to the Human Antimicrobial Peptide LL-37

Abstract: Pathogenic bacteria have evolved numerous mechanisms to evade the human immune system and have developed widespread resistance to traditional antibiotics. We studied the human pathogen Neisseria meningitidis and present evidence of novel mechanisms of resistance to the human antimicrobial peptide LL-37. We found that bacteria attached to host epithelial cells are resistant to 10 M LL-37 whereas bacteria in solution or attached to plastic are killed, indicating that the cell microenvironment protects bacteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 30 publications
(29 reference statements)
4
60
0
2
Order By: Relevance
“…The plasmid pJET1.2-⌬PilU_C was then introduced into the chromosome of the pilU mutant by transformation. To generate the pilT pilU double mutant strain, the FAM20 ⌬PilU strain was transformed with genomic DNA extracted from a previously constructed pilT-negative strain (13). Because pilT-negative Neisseria meningitidis cells are nontransformable, the pilU-complemented pilT pilU double mutant was generated by transforming the ⌬pilU_C strain in an identical manner.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid pJET1.2-⌬PilU_C was then introduced into the chromosome of the pilU mutant by transformation. To generate the pilT pilU double mutant strain, the FAM20 ⌬PilU strain was transformed with genomic DNA extracted from a previously constructed pilT-negative strain (13). Because pilT-negative Neisseria meningitidis cells are nontransformable, the pilU-complemented pilT pilU double mutant was generated by transforming the ⌬pilU_C strain in an identical manner.…”
Section: Methodsmentioning
confidence: 99%
“…Because the capsule is an important factor during adhesion to both biotic and abiotic surfaces (54), we sought to investigate the status of the capsule further. To determine whether these changes in expression affected the capsule in the ⌬pnp mutant, the amount of capsule was measured using whole-cell ELISA, as described previously (46). The ELISA revealed that there was no significant change in the amount of capsule present on the bacterial surface (Fig.…”
Section: Nmc0710 Is a Pnpase Homologmentioning
confidence: 99%
“…Capsular polysaccharides were quantified using whole-cell enzyme-linked immunosorbent assays (ELISA) with a monoclonal anti-serogroup C capsule antibody (code 95/678; National Institute for Biological Standards and Control), as described previously (46). Purified serogroup C polysaccharides (code 07/318; National Institute for Biological Standards and Control) were used as the positive control.…”
Section: Analysis Of Pnp Expression By Quantitative Real-time Pcr (Qpmentioning
confidence: 99%
“…Moreover, there is evidence that the MenB capsule is important for meningococcal survival within human cells, and that capsular biosynthetic genes are upregulated in the intracellular environment (6). There is also evidence that the meningococcal capsule contributes to protect the bacteria against cationic antimicrobial peptides (CAMP), including the human cathelicidin LL-37 (6,7), while at the same time, by interacting with the capsule, LL-37 seems to inhibit the proinflammatory activity of the capsular polysaccharide (8). On the other hand, the expression of the capsular polysaccharide inhibits the colonization and invasion of the nasopharyngeal barrier by masking the meningococcal adhesins/invasins (9).…”
mentioning
confidence: 99%